Personal correspondence - Pilcher, Hugh; Fagence, Maurice; Abrahams, Peter (My University, 1983)
Personal correspondence between Peter Abrahams and various unidentifiable correspondents
64 pgs. Typescript and handwritten, sepia-toned, fragile condition
Keywords: Abrahams, Peter, 1919-2017 - Correspondence.; Abrahams, Peter, 1919-2017.; Letters